The Influence of Social Media on University Students’ Self-Esteem - Zainuddin, Nurshahira Asyikin; Ravichandran, Venusha; Abd. Rahman, Rosshairy; Md Yusof, Zahayu (Universiti Putra Malaysia Press, 2022)
This study assessed the influence of social media on self-esteem among university students. Social media factors that affected the self-esteem of university students were investigated based on daily time spent on social media. Data were collected from an online questionnaire. Self-esteem was measured using the established Rosenberg Self-Esteem Scale. The quota sampling technique was deployed to select 381 undergraduate university students for this study. Descriptive analysis was performed to analyze the respondents’ demographic details, including gender, race, and age. Correlation and regression analyses were executed using SPSS software to test the correlations between social media factors and self-esteem among undergraduate students. As a result, self-esteem among the students was not significantly influenced by the amount of time they spent on social media. Therefore, more studies are in need to further investigate the main factors that influence the self-esteem of university students